The inglorious years: the collapse of the industrial order and the rise of digital society - Cohen, Daniel (Princeton University Press, 2021)
Modern mythologies -- Lost illusions (1/3) -- The conservative revolution -- The proletariat's farewell -- Immigration phobia -- The great hope of the twenty-first century -- iGen.